Second philosophy a naturalistic method - Maddy, Penelope (Oxford : Oxford University Press, 2007)
Many philosophers these days consider themselves naturalists but it's doubtful any two of them intend the same position by the term. Here, Penelope Maddy proposes a particularly austere form of naturalism called 'Second Philosophy'.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Naturalism; Mathematics -- Philosophy